2021
DOI: 10.1097/md.0000000000026546
|View full text |Cite
|
Sign up to set email alerts
|

Financial burden of postoperative complications following colonic resection

Abstract: Background: Colonic resection is a common surgical procedure that is associated with a high rate of postoperative complications. Postoperative complications are expected to be major contributors to hospital costs. Therefore, this systematic review aims to outline the health costs of postoperative complications following colon resection surgery. Methods: MEDLINE, Excerpta Medica database, Cochrane, and Economics literature medical databases were searched from 2010 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
(381 reference statements)
0
6
0
1
Order By: Relevance
“…One large cohort review concluded that 23.3% of patients undergoing colorectal surgery were readmitted to hospital [ 14 ]. This results in a huge economic burden and has been evidenced widely across many studies [ 15 ]. With the population ageing, these costs are expected to increase up to 10% each year [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…One large cohort review concluded that 23.3% of patients undergoing colorectal surgery were readmitted to hospital [ 14 ]. This results in a huge economic burden and has been evidenced widely across many studies [ 15 ]. With the population ageing, these costs are expected to increase up to 10% each year [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This figure mirrors Australia’s gross domestic product healthcare costs, amounting to 10% [ 1 , 2 ]. Growing expectations to deliver high-quality care compounded by increasing healthcare costs have prompted policymakers to change the paradigm by performing high-quality economic assessments [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review including 34 studies reports that postoperative complications are associated with a greater incidence of hospital readmission and that surgical site infections and anastomotic leaks are associated with greater resource utilization relative to other postoperative complications following colon resection surgery [ 9 ]. Anastomotic leaks have serious clinical-economic and health care utilization implications.…”
Section: Introductionmentioning
confidence: 99%
“…Colon surgery is a common procedure with a high rate of postoperative adverse events that are expected to substantially contribute to hospital costs [ 9 ]. Studies comparing conventional laparoscopic and robotic-assisted minimally invasive colon surgery show that both techniques are safe, feasible, and demonstrate comparable outcomes, but that robotic-assisted surgery significantly increases costs [ [42] , [43] , [44] , [45] , [46] ].…”
Section: Introductionmentioning
confidence: 99%